Epistemically unwarranted beliefs scale, development and evidence of validity in the Chilean population - Rodrigo Ferrer-Urbina; Herman Elgueta; Marcos Carmona-Halty; Geraldy Sepúlveda-Paez; Karina Alarcón-Castillo (PLoS ONE, 2025)
The study of epistemically unwarranted beliefs (EUB) (i.e., paranormal, pseudoscientific and conspiracy beliefs) has become relevant due to the negative effects they have produced on people’s health, as evidenced in the covid-19 pandemic. However, there is no instrument with appropriate and updated validity evidence for its evaluation in Latin American people. Because of this, the present study aims to develop a brief scale to analyze general epistemically unwarranted beliefs that do not depend on local factors. A total of 634 adults from five Chilean cities participated in the study of whom 93.8% (n = 575) were university students. Exploratory and confirmatory factor analyses revealed that the final structure of the Epistemically Unwarranted Beliefs Scale (EUBS) considers 9 items with three related factors. In addition, results showed good internal consistency (CFI > .95; TLI > .95; RMSEA < .07), gender invariance, and evidence of validity based on the inverse relation with the cognitive reflection test and the relationship with sociodemographic variables (i.e., gender, political orientation, and religious orientation). Finally, implications for the theoretical construct and possible limitations of the scale are discussed.